Memprediksi Produksi Boba Di Xing Fu Tang Di Centre Point Mall Medan Mengguanakang Metode Fuzzy Mamdani - Sanjaya, Roma (CV. Graha Mitra Edukasi, 2022)
PT. BOBA BAHAGIA MEDAN or known as XING FU TANG is an outlet that sells BOBA drinks, after the success of its first grand opening in 2018 last year at Lippo Plaza Mall Medan. Now it has several outlets in Medan Malls, one of which is at Center Point Mall Medan. With sales that can be said to be quite busy at one of the outlets in Center Point Mall Medan. Of course it is very interesting to do research with the title